RECOMMENDATIONS OF THE ALZHEIMER'S DISEASE INTERNATIONAL CONCERNING THE CARE OF PATIENTS WITH DEMENTIAAND THE SITUATION IN POLAND - Agnieszka Krawczyk-Wasielewska; Roksana Malak; Ewa Mojs; Włodzimierz Samborski; José C. Millán-Calenti; Ana Maseda; Rikke Gregersen; Kirsten Maibom (European Scientific Journal, ESJ, 2014)
According to data of WHO research, there are an estimated 36,5 million people with dementia worldwide. They need long-term care. The nature of this care depends on economic situation of the country - the higher developed it is, the bigger participation of institutions specialized in long-term care and smaller participation of home care. In high income countries around one-third to one-half of people with dementia are cared for in care homes. Alzheimer's Disease International (ADI) predicts that by 2030 number of patients with dementia will double and triple by 2050. This prognosis requires advanced planning, monitoring and coordination actions to improve system of long-term care. To achieve this goal, ADI recommends: promoting broad public awareness of dementia and combating stigma, identifying dementia capable support services at all stages of the disease, assessing and improving the quality of health care, social care and long-term care support and services, assessing availability and access to diagnostic services, promotion of brain health. Caregivers should be valued by society for they demanding and difficult work. Also patients should keep their autonomy and choice. 92% of suffering from dementia patents in Poland are cared at home since beginning of disease until their death. Other 8% stays at different types of home cares. There are also short-term care, daily care and ambulatory care available. The reasons of small participation of those institutions are: maladjusted to growing number of patients with dementia system of care, complicated administrative procedures, lack of money to cover up costs of care and lack of knowledge about dementia in society.